Occlusion and temporomandibular disorders - Semchyshyn, Я. О. (Actual Dentistry, 2023)
Summary. Clinicians and researchers have considered occlusion as one of the main direct and/or indirect etiological factor that cause temporomandibular disorders (TMD) for many years. The relationship between occlusion and TMD (temporomandibular disorders) has been based on the observation of an anatomical relationship between tooth position and jaw function for a long time, as well as on the higher prevalence of TMD in people with malocclusion compared to the general population. A significant number of studies have examined factors associated with occlusion and malocclusion as a potential mechanism for the development of signs or symptoms of TMD. At the same time, there are other concepts for the development of TMJ pathology. Aim of the research: to analyze modern views on the etiological factors of temporomandibular disorders according to the latest sources of scientific and medical information. Recent scientific trends have shifted the focus of TMD etiology from biomedical to a more complex multi-factor biopsychosocial model that includes biological, psychological, and social factors. Therefore, a proper understanding of the relationship between «occlusion» and SNA seems extremely important, since a paradigm shift requires a more comprehensive interpretation of the concepts of occlusion and maxillary relationships. The role of malocclusion in the etiology of temporomandibular disorders should be considered limited, unless a causal relationship is proven. Instead, clinicians should pay serious attention to patients «occlusal awareness» and concerns during general and dental consultations, as some patient groups may develop iatrogenic maladaptive behavior.